LETRAMENTO LITERÁRIO E CÍRCULOS DE LEITURA: UMA INTERVENÇÃO PEDAGÓGICA COM ESTUDANTES DOS ANOS FINAIS DO ENSINO FUNDAMENTAL - Carús, Cadia Mara Dorneles (2024)
In a literate society, understanding texts is an essential element of human rights, fundamental for acquiring wisdom and benefiting from the vast cultural and scientific heritage available. However, many children, teenagers, and adults in Brazil are deprived of this right. This study aims to investigate the contributions of a pedagogical intervention based on the formation of reading circles in a school environment. The research relates to the author's interest as a Portuguese language teacher in the final years of elementary school, who observes the need to educate students as readers by encouraging the reading of literary works. The study is characterized as a pedagogical intervention research with a qualitative approach. In the initial stage, the methodological delineation was carried out, which initially involved a bibliographic research to explain the concepts of literacy, literary literacy, and their implications regarding the importance of literature in the readers’ formation and the relevance of the teacher as a mediator. The second stage is characterized by the creation of a Reading Club during after-school hours, with the participation sixth-grade students from a public school in the municipality of Santa Maria, RS. The pedagogical practice followed the format of reading circles, proposed by Cosson (2021a and 2022a), based on the literary work "Matilda e o Clube de Leitura" (Trevisan, 2022). The third stage of the research involves the analysis of reading diaries and student self-assessment forms. This study revealed that the implementation of a Reading Club in the school environment and the use of reading circles as a pedagogical strategy can foster and maintain a love for literary reading, enabling more effective participation of students in reading and writing activities. It is concluded that the critical formation of the reader emerges from the space given to literary reading in the school context, in a movement of sensitization, contemplation, and reflection on literary works.